A dynamic reconfigurable nonlinear energy sink. (3rd March 2021) - Yang, Tianzhi; Hou, Shuai; Qin, Zhao-Hong; Ding, Qian; Chen, Li-Qun
Abstract: Traditional nonlinear energy absorbers, such as the nonlinear energy sink (NES) and negative stiffness vibration isolators, are not configurable. Therefore, when their structures have been fabricated, their performances cannot be tunable in real time, which prevents the application of these devices over a wider range external forcing amplitude. In this paper, we present a novel energy absorber that essentially offers nonlinearity and a time-dependent inertial mass. The newly designed mass is engineered using a three-body system, which consists of a primary mass and two additional masses that rotate along a circular orbit and offer an additional degree of freedom for dynamic modulation of the absorber. The resonant frequency can be modulated dynamically by using the angular velocity to trigger a controlled target energy transfer (TET). In particular, it is found that the maximum energy absorption limit can be overcome and that a much lower threshold for triggering of TET is supported. These results provide a new framework for the design of nonlinear vibration isolators and absorbers.